Influencing Factors on Consumer's Perception: On-site to OnlineDuring Covid-19 Pandemic in Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The midst of Covid-19, Thailand has been hit with lock down on the department stores. Thegovernment announce lockdown along with the uncertain situations of the Covid-19pandemic have caused both business and consumer change their shopping behavior. Thissituation has been affecting the urban lifestyle among consumers who enjoys going todepartment store. The objective of this study is to investigate the influencing factors thataffect the consumer’s perception on visiting the department store. The statistical analysis onfactor analysis was conducted with 400 questionnaires. The questionnaires focus on thedecision on the decision of the consumer’s consumption during Covid-19. This study aims toinvestigate 4 factors which are services of the mall, consumers’ satisfactions, Modernizationof the shopping malls, and public relations of the shopping mall. The results finding suggestthat social media online has significant influent factor to the consumer’s perception on theirdecision of department store services.This research can assist business in adapting to the newuncertainty situation of pandemic.